ANALISIS PENGARUH EFEKTIVITAS MODAL KERJA LEVERAGE TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG GO PUBLIK DI INDONESIA (STUDI KASUS PT. GUDANG GARAM TBK PERIODE TAHUN 2015-2019) - Muhiddin, Sarmila; Arfianty, Arfianty; Triastuti, Irin (DECISION : Jurnal Ekonomi dan Bisnis, 2022)
This study is a research with a quantitative approach. The population of this study is a manufacturing company listed on the Indonesia Stock Exchange in the tobacco factory sub-sector and the sample obtained is PT Gudang Garam Tbk for the 2015 – 2019 period. The data analysis method used is multiple regression. The data collection techniques used in this research are library research and documentation techniques. Data analysis techniques in this study used hypothesis testing. Based on the results of the research that has been done, it shows that: the effectiveness of working capital has an effect on profitability as indicated by the regression coefficient value of 0.017, so the first hypothesis is accepted. Leverage has a positive effect on profitability indicated by a regression coefficient of 0.012, so the second hypothesis is accepted. Simultaneously, the effectiveness of Working Capital and Leverage affect the Company's Profitability, thus the third hypothesis is accepted.